PH‐Controlled Formation of a Stable β‐Sheet and Amyloid‐like Fibers from an Amphiphilic Peptide: The Importance of a Tailor‐Made Binding Motif for Secondary Structure Formation. Issue 49 (3rd November 2016) - Jana, Poulami; Ehlers, Martin; Zellermann, Elio; Samanta, Krishnananda; Schmuck, Carsten
Abstract: The new amphiphilic peptide1 is composed of alternating cyclohexyl side chains and guanidiniocarbonyl pyrrole (GCP) groups. In contrast to analogue2, which contains lysine instead of the GCP groups and only exists as a random coil owing to charge repulsion, peptide1 forms a stable β‐sheet at neutral pH in aqueous medium. The weakly basic GCP groups (p K a ≈7) are key for secondary structure formation as they stabilize the β‐sheet through mutual interactions (formation of a "GCP zipper"). The β‐sheets further aggregate into left‐handed helically twisted fibers. However, β‐sheet formation is completely reversible as a function of pH. At low pH (ca. 4), peptide1 is unstructured (random coil) as all GCP units are protonated. Only round colloidal particles are observed. The amyloid nature of the fibers formed at neutral pH was confirmed by staining experiments with Congo Red and thioflavin T. Furthermore, at millimolar concentrations, peptide1 forms a stable hydrogel. Abstract : Short amphiphilic peptides with guanidiniocarbonyl pyrrole (GCP) side chains adopt stable β‐sheet secondary structures at neutral pH, predominantly because of GCP–GCP interactions. β‐Sheet formation is completely reversible. Moreover, the β‐sheet‐forming peptides form cationic amyloid fibers at pH 7 whereas at lower pH values (pH 4), the peptides adopt random coil structures and form vesicular structures.